Optimization Of Invitro Cultures And Effects Of Elicitation The Flavonoid Contents Of Pegaga (Centella Asiatica L. Urban) - Ong, Mei Kying (2008)
Secondary metabolites in Centella asiatica, especially flavonoids is known to possess strong antioxidative activity and widely investigated as a new source of active compound for health benefits. The flavonoids content in field planted Centella asiatica is very low, therefore high volume of Centella asiatica plant supply is needed to fulfill the increase demand for the active compounds as an important nutraceutical resources. The main aim of this research done was to obtain the most applicable, simplest and effective in vitro approaches that can increase the flavonoids content in Centella asiatica (CA05). Many research studies done have proved that flavonoids content can be successfully enhanced through elicitation. In this study, elicitation of important flavonoids such as catechin was investigated and their presence in various tissues of Centella asiatica (CA05) planted using various cultivation methods were assessed. The initial work involved the optimization of plantlet regeneration and root culture of Centella asiatica (CA05). Regeneration of Centella asiatica (CA05) from various explants is necessary in order to produce continuous supply of plant materials for further manipulation. In addition to in vitro plantlets and root culture, hydroponically grown plantlets were also used for flavonoids elicitation using biotic elicitors, namely chitosan and yeast extract. Various techniques of sterilization and media formulation using different plant growth regulators such as auxin and cytokinin were applied to regenerate the plant. The explants were sterilized using 30% Clorox (1.58% sodium hypochlorite) for 5 minutes (leaf), 30% Clorox (1.58% sodium hypochlorite) for 15 minutes (stem), 0.05% mercury chloride for 5 minutes and followed by 30% Clorox (1.58% sodium hypochlorite) for 20 minutes (seed) for 56.7% of viable leaf explant, 75.0% of viable stem explant and 48.3% of sterile seedlings, respectively. For plant regeneration, MS supplemented with 2.26μM Indole-3-acetic acid (IAA) and 2.26μM 6-Benzylaminopurine (BAP) exhibited 38.0% of shoot regeneration frequency from leaf explants. MS supplemented with 2.26μM Indole-3-butyric acid (IBA) showed rapid induction of root from stem (63.0%) after 7 days. In this study, the seed of Centella asiatica were treated with various techniques to break the seed dormancy. The hard seed were pretreated by scarification and soaking for various time regime. Effect of presoaking in MSO liquid medium for 1 day before culture gave the highest percentage means of germination (81.0%). High pressure liquid chromatography (HPLC) was used to determine the flavonoids in various Centella asiatica plant parts (root, stem, leaf) grown in vitro and hydroponics. Catechin is detected to be major flavonoids in Centella asiatica in addition to naringin, hesperidin, rutin and myricetin. Result from the study showed that in vitro plantlets contain high total flavonoids (4456.9 + 287.5 μg/g) compared to that of hydroponicsgrown plantlets (2401.0 + 148.4 μg/g) and that of field plant (2323.5 + 376.8 μg/g). In general, leaf of Centella asiatica was found to contain the highest flavonoids content compared to either root or stem. Effects of both elicitors, namely chitosan and yeast extract on flavonoids production were evaluated. Result of the study showed that root culture treated with 0.5 mg/l chitosan for one week showed the highest flavonoids (2968.2 + 66.1 μg/g) with 2.28 fold increase of catechin (128.1% higher than control). While, for the elicitation in in vitro plantlet with 5 mg/l chitosan in 1 week, the highest total flavonoids amount was recorded at 5530.6 + 385.5 μg/g with increase of 17.9% or 1.2 fold compared to control. Prolong exposure to elicitors up to four weeks did not show any increase of flavonoids content in all cultivated plant tissues. Therefore, it can be concluded that, flavonoids production was improved with chitosan elicitation, and it can be helpful in increasing the productivity of flavonoids.